3D optomechanical metamaterials - Münchinger, Alexander; Hsu, Li-Yun; Fürniß, Franziska; Blasco, Eva; Wegener, Martin (Materials today, 2022)
Ideally, many materials should have a “knob” that allows for changing its properties at will, including the possibility to flip the sign of its behavior. This “knob” could be used to continuously tune the properties or in the sense of a digital switch. Such extreme level of stimulus-responsiveness has come into reach with recently increased possibilities of manufacturing complex rationally designed artificial materials called metamaterials on the micrometer scale. Here, we present mechanical metamaterials composed of liquid-crystal elastomers, whose director field is arranged into a designed complex three-dimensional (3D) pattern during the 3D laser printing process. External light from a blue LED, with intensities in the range of 10-30 W/cm2, serves as the stimulus. In the first example, we repeatedly flip the sign of the Poisson’s ratio of an achiral architecture within classical elasticity. In the second example, we flip the sign of the twist per strain in a chiral metamaterial beyond classical elasticity. The presented examples overcome major limitations in responsive mechanical metamaterials and we foresee many possible three-dimensional responsive micro-architectures manufactured along these lines.
Dateiversion vom 17. November 2022
Gesehen am 07.02.2023